2015
DOI: 10.7883/yoken.jjid.2014.169
|View full text |Cite
|
Sign up to set email alerts
|

Ferret Hepatitis E Virus Infection in Japan

Abstract: SUMMARY:We examined 85 fecal samples from pet ferrets in 10 animal hospitals in Japan for the detection of ferret hepatitis E virus (HEV) RNA. We found that 6 (7.1z) of the samples were positive for ferret HEV RNA. Phylogenetic analysis based on the partial ORF1 indicated that these ferret HEV strains were clearly separated from the Netherlands strains and were divided into 2 distinct clusters. These results suggest that ferret HEV is genetically diverse, and since ferrets are not indigenous to Japan, ferret H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Orthohepevirus C is divided into HEV-C1, which has been isolated in several countries, including Germany, Australia, Belgium, Denmark, France, Italy, Spain, Switzerland, USA, Vietnam, Indonesia, China and Hong Kong ( Rattus spp. , greater bandicoot rat, Asian musk shrew) [38,39,79,80,81,82,83,84,85,86,87], and HEV-C2 (ferret [88,89], mink [40]).…”
Section: Taxonomymentioning
confidence: 99%
“…Orthohepevirus C is divided into HEV-C1, which has been isolated in several countries, including Germany, Australia, Belgium, Denmark, France, Italy, Spain, Switzerland, USA, Vietnam, Indonesia, China and Hong Kong ( Rattus spp. , greater bandicoot rat, Asian musk shrew) [38,39,79,80,81,82,83,84,85,86,87], and HEV-C2 (ferret [88,89], mink [40]).…”
Section: Taxonomymentioning
confidence: 99%
“…One of those is the ferret. A ferret strain of HEV was first described in the Netherlands in 2010 and now appears to be widespread around the world [111,146,147]. Ferret HEV is distinct from human HEV, shares the highest similarity with rat HEV, and is assigned to the Orthohepevirus C species [111].…”
Section: Other Small Animal Modelsmentioning
confidence: 99%
“…Ferrets (M. putorius), which have long been used as an animal model of influenza virus infection, may also be valuable for the study of www.perspectivesinmedicine.org HEV infection. HEV was first detected in ferrets from the Netherlands in 2012 (Raj et al 2012), but since then many other ferret HEV strains have been identified in ferrets used as laboratory animals or kept as pets in the United States and Japan (Raj et al 2012;Yang et al 2013;Li et al 2015b). Ferret HEV is distinct from human HEV and is widespread among ferrets in Europe, the Americas, and Asia.…”
Section: Ferrets (Mustela Putorius)mentioning
confidence: 99%